A dynamic relative displacement evaluation method for extra‐high voltage transformer withstanding short‐circuit impact. Issue 6 (2nd January 2023) - Ou, Qiang; Luo, Longfu; Li, Yong; Lin, Yantao; Tian, Ye
Abstract: The extra‐high voltage (EHV) transformer winding disks are subjected to dynamic electromagnetic forces caused by short‐circuit currents. These periodically decaying impact forces may endanger the safety of the transformer. The winding constraint conditions around the circumference are different due to the influence of axial pressure structures and magnetic boundaries. Moreover, this difference becomes more evident as the voltage and capacity increase. To investigate the spatial differences and time effects of EHV transformer short‐circuit faults, this paper proposes a reliability evaluation method based on dynamic relative displacement (DRDEM) for the first time. Firstly, the suitable and efficient analysis method is summarized by comparing the deviation among different calculated impedances and the measured value. Then, the space‐time effect of windings is obtained by the static magnetic field and dynamic structural field based on equivalent compression supports. Furthermore, a 50 MVA/110 kV transformer is designed for the destructive short‐circuit test to simulate the short‐circuit ability feature of the EHV transformer. The disassembly phenomena after all the tests indicate that the DRDEM is more adaptable in characterizing the winding ability to withstand short circuit when investigating the spatial differences and time effects. Abstract : This paper proposes a reliability evaluation method based on dynamic relative displacement (DRDEM) for the first time. A 50 MVA /110 kV transformer is developed for the destructive short‐circuit test to simulate the short‐circuit ability feature of the EHV transformer. The disassembly phenomenon after all the tests indicates that the DRDEM is more adaptable in characterizing the winding ability to withstand short circuit when considering the spatial differences and time effects.